PP531 Quality Of Life Of Patients With Long-Chain Fatty Acid Oxidation Disorders Before And During Treatment With Triheptanoin. (December 2020) - Kruger, Eliza; Marsden, Deborah; Bensimon, Arielle; Cook, Erin; Orvis, Eli; Yang, Hongbo; Mayhew, Jill; Thomas, Nina
Abstract : Introduction: Long-chain fatty acid oxidation disorders (LC-FAOD) are a group of serious diseases in which patients are at risk of metabolic decompensation, resulting in cardiomyopathy, hypoglycemia and rhabdomyolysis and premature mortality. In addition, LC-FAOD are a burdensome disease that adversely effects quality of life (QoL) via symptoms of muscle pain, fatigue, and a difficult diet. Previous studies have reported improvements in QoL during treatment with triheptanoin as measured by short form (SF) instruments. This study sought to convert the QoL measure into a utility value for a sample of patients with LC-FAOD at baseline and 78 weeks during treatment with triheptanoin. Methods: In an open-label Phase 2 study of triheptanoin (UX007-CL201, NCT01886378), caregivers of patients (n = 9/23 enrolled) or patients aged 18+ years (n = 6/6 enrolled) completed the SF-10 or the SF-12v2, respectively. Component summary scores at baseline and 78-week during treatment period were converted to EuroQol-Five Dimension (EQ-5D) utility (with zero representing death and 1.0 perfect health) using a published conversion algorithm (Lawrence and Fleishman 2004). Generalized linear mixed-effects models with individual-level random effects were used to estimate the utility values. Results: At baseline, patients' utility was estimated to be 0.365 (standard error [SE] = 0.090) compared with 0.629 (SE = 0.072) 78-weeks during treatment, a significant improvement (p = 0.0073). In a sensitivity analysis using SF-12v2 data only (that is, only adult patients), utility estimates were 0.498 (SE = 0.084) at baseline versus 0.690 (SE = 0.068) during treatment (p = 0.0499). No patients had a major clinical event during the SF instrument recall period, indicating the benefit was driven by day-to-day improvement in QoL. Conclusions: Treatment with triheptanoin resulted in a substantial improvement in daily QoL for patients with LC-FAOD. Limitations of this study include that the estimation of utilities is from a single-arm study with small sample sizes and that the assessment of utility was based on a conversion algorithm rather than direct measurement. Nevertheless, results indicate significant improvement in QoL for patients treated with triheptanoin.